Congenital pulmonary lymphangiectasis associated with pleural effusions. Issue 3 (March 1984) - Hunter, W S; Becroft, D M
Abstract : We report a case of congenital pulmonary lymphangiectasis in which pleural effusions were shown antemortem by thoracentesis. We suggest that disordered lymphatic drainage led to the production of the effusions.